Analisis Metakognitif Melalui Media Pada Matakuliah Seni Rupa Mahasiswa Pendidikan Guru Sekolah Dasar: Metacognitive Analysis Through Media in Fine Arts Courses Education for elementary school teachers - Wati, Tri Linggo (Universitas Muhammadiyah Sidoarjo, 2020)
This research is a descriptive study that aims to analyze the effective application of metacognitive through instructional media, the meticulous subjects used in this study are 3 students who have high, medium, low ability. What was done in the Elementary School Education Study Program of the University of Muhammadiyah Sidoarjo. The theory used is Slavin's metacognitive theory and the theory of the effectiveness of learning using Dunn's theory. Test the validity of the data using triangulation techniques, namely observation, documentation, and interviews. The results of the analysis obtained from this study were, subject A did metacognitive thinking and the existing media proved to be effective in helping metacognitive way of thinking, whereas in subject B the metacognitive way of thinking had been done only in the process of monitoring and evaluation was still lacking, the use of media on the object image said the subject helps in the process of his work. While the subject C metacognitive thought process has been carried out, only the evaluation process is still lacking, while the existing media helps in the process of metacognitive thinking. So it can be concluded that the media is very effective in helping the application of metacognitive thinking in producing two-dimensional works of art in students of elementary school teacher study programs at the University of Muhammadiyah Sidoarjo.